44. CLINICAL CHARACTERISTICS OF WORKERS WITH PNEUMOCOSIS BEING TREATED IN NATIONAL LUNG HOSPITAL IN 2022-2023 (Vietnam Journal of Community Medicine, 2024)
Aims of review: Describe the paraclinical symptoms of workers with pneumoconiosis treated at the Central Lung Hospital in 2022-2023.Research method: A descriptive study with purposive sampling was conducted at the Department of Occupational Lung Diseases, Central Lung Hospital on all 60 patients with pneumoconiosis who met the selection criteria.Results and conclusion: Generally, subclinical symptoms can be observed on chest X-ray results according to ILO 2011 standards and lung ventilation function testing. Chest X-ray: lung parenchymal lesions are mainly small opacities with size p (20.0%), the main subgroup is small opacities with density 1 (45%); 26.7% of patients had large opacities (type A large opacities accounted for the highest proportion with 15.0%; type B accounted for 10.0% and type C was rarer with 1.7%). Exploration of ventilatory function: mainly encountered patients with limited erectile dysfunction (23.3%), obstructive erectile dysfunction (33.3%), and mixed erectile dysfunction (1.7%). Of these, 20% have mildly limited neuropathy; 16.67% of patients had moderate obstructive erectile dysfunction; Patients with mixed erectile dysfunction account for only 1.67%. It is necessary to diagnose pneumoconiosis early and carry out lifelong monitoring and management of pneumoconiosis according to the instructions of the health sector.
Keywords: Workers, pneumocosis, subclinical symtoms.